Wefix : Mobile Application for Repair Shop Finder - Ahmad Anwar Ariffin, Mohammad (Universiti Malaysia Sarawak (UNIMAS), 2020)
The domination of e-commerce industry is sided to product based business whereas the service oriented business for small-to-medium sized enterprises (SME) is still lagging behind in this competitive industry. The most popular e-commerce platform in Southeast Asia such as Shopee and Lazada have recorded 200 million and 174 million in total for mobile web and desktop visits respectively. The overwhelming number of visits is due to the effective strategies an approaches applied by these giant online marketplace. The overwhelming number of visits is due to the effective strategies an approaches applied by these giant online marketplace. In this project, an application called WeFix has been proposed to serve as a platform for business owner who wants to promote their services to local community in Kota Samarahan. The services offered is mainly for repairing related service such as electronic devices, home appliances and vehicles and it is targeted for residential areas within Kota Samarahan.